2009
DOI: 10.4103/0973-8258.59732
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the anti-arthritic activities of the plantsJusticiagendarussaburm F. andWithaniasomniferalinn

Abstract: The aim of this study was to compare the anti-arthritic activities of the plants Justicia gendarussa and Withania somnifera. Arthritis is induced in male albino rats using Freund's complete adjuvant and bovine type II collagen. Leaves of J. gendarussa and roots of W. somnifera were powdered and extracted with ethanol (95%) using the soxhlet method. The effect of these plant extracts on arthritic rats were assessed by various blood parameters and also by taking the change in paw volume. The plants J. gendarussa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…This may be attributed to amelioration in the condition of animals by reducing inflammation associated with arthritis. In previous studies, it has been reported that there is remarkable reduction in the body weight of adjuvant-injected animals in contrast to vehicle control rats. Justicia gendarussa and Withani somnifera significantly ameliorated the body weight as compared to disease control rats in both collagen- and CFA-induced arthritic animals . It has been described in another previous study that rats in the disease control group lose body weight in contrast to rats administered with Mesua ferrea …”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This may be attributed to amelioration in the condition of animals by reducing inflammation associated with arthritis. In previous studies, it has been reported that there is remarkable reduction in the body weight of adjuvant-injected animals in contrast to vehicle control rats. Justicia gendarussa and Withani somnifera significantly ameliorated the body weight as compared to disease control rats in both collagen- and CFA-induced arthritic animals . It has been described in another previous study that rats in the disease control group lose body weight in contrast to rats administered with Mesua ferrea …”
Section: Discussionmentioning
confidence: 65%
“…Justicia gendarussa and Withani somnifera significantly ameliorated the body weight as compared to disease control rats in both collagen-and CFA-induced arthritic animals. 49 It has been described in another previous study that rats in the disease control group lose body weight in contrast to rats administered with Mesua ferrea. 45 It has been stated that CFA injection evokes T cells that trigger monocytes and macrophages, thus producing proinflammatory cytokines like IL-1β, TNFα, and IL-6, which accelerate bone erosion, joint damage, and cell death in the joints of arthritic rats.…”
Section: Discussionmentioning
confidence: 93%
“…The extract (95% ethanolic extract) obtained from the plant leaf Justicia gendarussa shows the action against arthritic in FCA (Freund's complete adjuvant) induced arthritis in male albino wistar rats at concentration of 100mg/kg (Paval et al, 2009b). Ethanolic (95%) plant extract of leaves Justicia gendarussa shows the activity against arthritis in FCA (Freund's complete adjuvant) and also in bovine type II collagen induced arthritis in male albino wistar rats at the dose of 100mg/kg (Paval et al, 2009a).…”
Section: Anti-arthritic Activitymentioning
confidence: 99%
“…The C-reactive protein (CRP) and serum copper CRP levels estimated using the enzyme-linked immunosorbent assay kit (obtained from Alpha Diagnostic Intl., USA) and the colorimetric bathocuproindisulfonate method of Zak and Landers, respectively. [43,44] Statistics All values are shown as mean ± standard error of the mean. Statistical analysis was performed using one-way analysis of variance followed by Dunnett's test.…”
Section: Complete Freund's Adjuvant-induced Arthritis In Ratsmentioning
confidence: 99%